Deals and development : the political dynamics of growth episodes - Pritchett, Lant, Ed (Oxford University Press, 2018)
When are developing countries able to initiate periods of rapid growth and why have so few been able to sustain growth over decades? This book provides a novel conceptual framework built from a political economy of business-government relations and applies it to nine countries across Africa and Asia, drawing actionable policy recommendations.